Sentiment indices on financial markets: What do they measure? - Sven-Kristjan Bormann (Kiel Institute for the World Economy (IfW), 2013)
Sentiment indices based on investor sentiment surveys attempt to measure the stock market sentiment. The literature on these indices focusses mainly on whether investor sentiment influences the financial markets or not. But the term 'sentiment' has never been defined in the literature. Therefore it is unclear what is measured by sentiment indices, whether it is really sentiment or something different. This paper closes this gap in the literature by using psychological definitions about feelings to explain what might be meant by 'market sentiment'. It shows how useful these definitions are with data from the German sentiment index 'Sentix'. The paper contributes to the current discussion in three ways: 1. It presents a simple concept of sentiments in general. 2. It relates short and long term sentiment indices to two distinct parts of sentiments, emotion and mood. 3. It extracts two factors representing investor emotion and mood across all markets in the dataset. These results are stable across markets and model specifications in the Sentix dataset.
Keywords: G02; G14; 330; sentiment indices; investor sentiment; factor analysis; psychological analysis; financial markets